SafeHer App: Empowering Women with Accessible Safety Tools and Resources - Bhandare, Harshda; Rajmane, Siddhi; Patil, Nikita; Mane, Vaishnavi (International Journal of Computer Sciences and Engineering, 2024)
The "SafeHer" application is designed to empower women by equipping them with indispensable tools for personal safety. These include one-tap emergency alerts, GPS tracking, live location sharing, siren activation, voice recording, helpline integration, and an innovative feature that allows users to shake their phone to automatically share their live location every 30 seconds. Additionally, the app enables reporting of unsafe areas, accessing local emergency resources, and fostering connections with nearby women for mutual safety. The application aspires to mitigate risks of violence, cultivate a supportive community, and fortify women`s confidence and well-being. By leveraging this platform, women can not only access safety resources more effectively but also establish direct connections with safety service providers. This can be emphatically asserted to prompt structural reforms within the safety support ecosystem, thereby amplifying women`s security within society. The study underscores the critical role of mobile technology in addressing pervasive safety challenges faced by women. These challenges include limited accessibility to assistance and inadequate awareness of available resources. To address these vulnerabilities, the application integrates an array of safety-centric features and facilitates direct interaction with safety services.